Analisis Aktor Berpengaruh Dan Aktor Popular Dengan Metode Degree Centrality Dan Follower Rank Pada Tagar Twitter “#gejayanmemanggil” - Adang Rochiyat; Arief Wibowo (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2020)
The use of Twitter as a social networking media is currently growing rapidly not only used to convey feelings about themselves but can also convey opinions and feelings they feel related to problems that are happening. Twitter is currently considered social media that can be analyzed on the elements of social networking (social network analysis). One study that can be done is the analysis of user accounts (actors) on Twitter. In this research, an analysis has been carried out to find out who the influential actor is and how popular the actor is, on Twitter. The method used for the analysis of influential actors is degree centrality while the analysis of popular actors uses the follower rank method. Case studies were conducted on tweet data containing the hashtag "#gejayanmemanggil". The results showed that RyanResttu is the actor who has the highest influence value with the degree of centrality value of 0.108072 and the actor TirtoID is an actor who has high popularity with a follower rank value of 0.999880312. This research ignores the existence of buzzer accounts on Twitter. However, actors who have high influence value are not necessarily those who have high popularity values.